2021
DOI: 10.3390/ma14071640
|View full text |Cite
|
Sign up to set email alerts
|

Surface Finish Analysis in Single Point Incremental Sheet Forming of Rib-Stiffened 2024-T3 and 7075-T6 Alclad Aluminium Alloy Panels

Abstract: The article presents the results of the analysis of the interactions between the single point incremental forming (SPIF) process parameters and the main roughness parameters of stiffened ribs fabricated in Alclad aluminium alloy panels. EN AW-7075-T6 and EN AW-2024-T3 Alclad aluminium alloy sheets were used as the research material. Panels with longitudinal ribs were produced with different values of incremental vertical step size and tool rotational speed. Alclad is formed of high-purity aluminium surface lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The tool is specifically mounted at an angle of 30° degrees, so that the mechanical momentum sensor STJ100 ( 7) is connected to controller BGI (8) (Mark-10 Corp., Copiague, NY, USA) and could measure both-pressing and friction momentum. The sensor controller BGI is connected to an oscilloscope PicoScope 3424 (9) (Pico Technology Ltd., St. Neots, UK, GB), which transmits the results obtained from the mechanical moment sensor on the computer (10). The parameters of the tool forming path trajectory are given in Table 2.…”
Section: Experimental Investigation Of Robotized Incremental Aluminum Sheet Formingmentioning
confidence: 99%
See 2 more Smart Citations
“…The tool is specifically mounted at an angle of 30° degrees, so that the mechanical momentum sensor STJ100 ( 7) is connected to controller BGI (8) (Mark-10 Corp., Copiague, NY, USA) and could measure both-pressing and friction momentum. The sensor controller BGI is connected to an oscilloscope PicoScope 3424 (9) (Pico Technology Ltd., St. Neots, UK, GB), which transmits the results obtained from the mechanical moment sensor on the computer (10). The parameters of the tool forming path trajectory are given in Table 2.…”
Section: Experimental Investigation Of Robotized Incremental Aluminum Sheet Formingmentioning
confidence: 99%
“…One of the indicators of the quality of the formed product is the surface quality [ 10 , 11 , 12 , 13 , 14 , 15 ]. The authors in [ 10 ] present the results of an analysis of the interaction between the SPIF process parameters and the stiffened ribs made of Alclad aluminum alloy plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, an increase has been observed in works related to the incremental forming of the following lightweight alloy sheets: titanium and titanium alloys [30,31], aluminium alloys [32,33] and magnesium and its alloys [34]. These works are mainly related to the use of these alloys in the aviation [32] and space [35] industries, where, increasing, the share of lightweight metals in the entire structure is part of the efforts to reduce carbon dioxide emissions to the atmosphere. A brief overview of the stateof-the-art methods of incremental sheet forming for lightweight materials was provided by Trzepieci ński et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, machine learning techniques with controlled manufacturing are used to develop various effective predictive models [ 25 , 26 , 27 , 28 , 29 ]. Trzepieciński et al [ 30 ] presented an analysis of the interaction between SPIF process parameters and the main roughness parameters. They found that predictive models of ANNs for Ra and Rz were characterised by performance measures of R 2 values between 0.657 and 0.979.…”
Section: Introductionmentioning
confidence: 99%